Cusk-eel confusion: revisions of larval Luciobrotula and Pycnocraspedum and re-descriptions of two bythitid larvae (Ophidiiformes) - Matthew G. Girard; Bruce C. Mundy; Ai Nonaka; G. David Johnson (Ichthyological Research, 2023)

Distribution and structure of deep-sea demersal fish assemblages across the central and western Pacific Ocean using data from undersea imagery - Gina M. Selig; Jeffrey C. Drazen; Peter J. Auster; Bruce C. Mundy; Christopher D. Kelley (Frontiers in Marine Science, 2023)
Demersal deep-sea fish assemblages from islands and seamounts are poorly described, even in the Hawaiian archipelago. Knowledge across all depths, in similar settings, is even sparser for other archipelagos in the central and western Pacific. However, recent remotely operated vehicle (ROV) explorations and archived video from human-occupied submersible dives conducted by the Hawai`i Undersea Research Laboratory (HURL) provide an opportunity to explore the structure of these assemblages. Here we describe demersal fish assemblages across the central and western Pacific, including in four Marine National Monuments, and examine the relationship of the assemblages to depth and environmental conditions. We used data collected from 227 underwater vehicle dives resulting in the identification of 24,837 individuals belonging to 89 families and 175 genera. The most frequently occurring genera at depths of 250-500 m were Epigonus , Setarches , Polymixia , and Antigonia , between 500-1000 m were Chlorophthalmus , Aldrovandia , and Neocyttus , and between 1000-3000 m were Synaphobranchus , Kumba , Halosaurus , Ilyophis , and Ipnops . There are strong changes in the fish assemblages with depth and region, and assemblages become more similar between regions with greater depth. Depth and region explained the most variance in assemblage structure followed by seafloor particulate organic carbon flux (a food supply proxy), concentrations of dissolved oxygen, and salinity. The Line Islands and Tokelau Ridge had the highest values of seafloor particulate organic carbon flux for all depth zones investigated (250-3000 m) and the highest abundance of fishes at 250-500 m and 500-1000 m, respectively. Taxon accumulation curves indicated that diversity at the genus level within all regions and depth bins (except 1000-2000 m and 2000-3000 m) had not been reached with the existing sampling effort. However, when combining samples from all regions, diversity generally appeared to decrease with depth. Overall, this study demonstrates that there are significant regional differences in the composition of the deep-sea fish fauna as well as differences across depth. Such distribution patterns suggest that the four Marine National Monuments (Papahānaumokuākea, Marianas Trench, Pacific Remote Islands, and Rose Atoll Marine National Monuments, encompassing an area of 3,063,223 km 2 ) are not replicates of diversity, but complementary components of the regional fauna.

Vertical distributions of organic matter components in sea ice near Cambridge Bay, Dease Strait, Canadian Archipelago - Kwanwoo Kim; Sun-Yong Ha; Kyung-Hoon Shin; Jee-Hoon Kim; C. J. Mundy; Laura A. Dalman; Bo Kyung Kim; Dabin Lee; Hyo Keun Jang; Yejin Kim; Sanghoon Park; Sang Heon Lee (Frontiers in Marine Science, 2023)
Ice algae thriving within sea ice play a crucial role in transferring energy to higher trophic levels and influencing biogeochemical processes in polar oceans; however, the distribution of organic matter within the ice interior is not well understood. This study aimed to investigate the vertical distribution of organic matter, including chlorophyll a (Chl-a), particulate organic carbon and nitrogen (POC and PON), carbohydrates (CHO), proteins (PRT), lipids (LIP), and food material (FM), within the sea ice. Samples were collected from the bottom, middle, and top sections of the sea ice column near Cambridge Bay during the spring of 2018. Based on the δ 13 C signature, biochemical composition, and POC contribution of biopolymeric carbon (BPC), the organic substances within the sea ice were predominantly attributed to marine autotrophs. While the highest concentrations of each parameter were observed at the sea ice bottom, notable concentrations were also found in the upper sections. The average sea ice column-integrated Chl- a concentration was 5.05 ± 2.26 mg m −2 , with the bottom ice section contributing 59% (S.D. = ± 10%) to the total integration. The column-integrated concentrations of FM, BPC, POC, and PON were 2.05 ± 0.39, 1.10 ± 0.20, 1.47 ± 0.25, and 0.09 ± 0.03 g m −2 , respectively. Contributions of the bottom ice section to these column-integrated concentrations varied for each parameter, with values of 20 ± 6, 21 ± 7, 19 ± 5, and 28 ± 7%, respectively. While the bottom ice section exhibited a substantial Chl- a contribution in line with previous studies, significantly higher contributions of the other parameters were observed in the upper sea ice sections. This suggests that the particulate matter within the interior of the sea ice could potentially serve as an additional food source for higher trophic grazers or act as a seeding material for a phytoplankton bloom during the ice melting season. Our findings highlight the importance of comprehensive field measurements encompassing the entire sea ice section to better understand the distribution of organic carbon pools within the sea ice in the Arctic Ocean.

Metabolomics approach reveals size-specific variations of blackfoot abalone (Haliotis iris) in Chatham Islands, New Zealand - Thao Van Nguyen; Andrea C. Alfaro; Leonie Venter; Jessica A. Ericson; Norman L.C. Ragg; Tom McCowan; Craig Mundy (Fisheries Research, 2023)

Hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) causes seizure activity in larval zebrafish via antagonism of γ-aminobutyric acid type A receptor α1β2γ2 - Paige C. Mundy; Alicia Werner; Latika Singh; Vikrant Singh; Rosalia Mendieta; Caitlyn E. Patullo; Heike Wulff; Pamela J. Lein (Archives of Toxicology, 2023)
Hexahydro-1,3,5-trinitro-1,3,5-triazine, or Royal Demolition Explosive (RDX), is a major component of plastic explosives such as C-4. Acute exposures from intentional or accidental ingestion are a documented clinical concern, especially among young male U.S. service members in the armed forces. When ingested in large enough quantity, RDX causes tonic–clonic seizures. Previous in silico and in vitro experiments predict that RDX causes seizures by inhibiting α1β2γ2 γ-aminobutyric acid type A ( GABA A ) receptor-mediated chloride currents. To determine whether this mechanism translates in vivo, we established a larval zebrafish model of RDX-induced seizures. After a 3 h of exposure to 300 µM RDX, larval zebrafish exhibited a significant increase in motility in comparison to vehicle controls. Researchers blinded to experimental group manually scored a 20-min segment of video starting at 3.5 h post-exposure and found significant seizure behavior that correlated with automated seizure scores. Midazolam (MDZ), an nonselective GABA A R positive allosteric modulator (PAM), and a combination of Zolpidem (α1 selective PAM) and compound 2-261 (β2/3-selective PAM) were effective in mitigating RDX-triggered behavioral and electrographic seizures. These findings confirm that RDX induces seizure activity via inhibition of the α1β2γ2 GABA A R and support the use of GABA A R-targeted anti-seizure drugs for the treatment of RDX-induced seizures.